PENGARUH EFEKTIVITAS PENERAPAN KEBIJAKAN PP NOMOR 55 TAHUN 2022 DAN SOSIALISASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK UMKM TAHUN 2023 DI KPP PRATAMA JAKARTA TANAH ABANG DUA - Ulum, Muhammad Bahrul; Wahyudin, Dian (Jurnal Ilmu Administrasi Publik, 2025)
There has been an increase in the number of SMEs, totaling 65 million units, which has not been accompanied by a corresponding level of tax compliance. Therefore, the government issued the PP No. 55 of 2022 regarding the exemption of the final income tax for SMEs with a turnover of less than IDR 500 million/year. This research aims to analyze the partial and simultaneous effects of the effectiveness of implementing policy PP No. 55 of 2022 and tax socialization on the tax compliance of SMEs at the KPP Pratama Jakarta Tanah Abang Dua. This research uses a descriptive quantitative approach with primary data collected through a survey questionnaire from 100 respondents. The data analysis techniques used include validity tests, reliability tests, descriptive statistical analysis, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression analysis, t-tests, f-tests, and the coefficient of determination test using the IBM SPSS Statistics 26. The results of this research indicate that the effectiveness of implementing policy PP No. 55 of 2022 has a partially positive and significant effect on the tax compliance of SMEs by 55.2%, tax socialization has a partially positive and significant effect on the tax compliance of SMEs by 64.6%, and the effectiveness of implementing policy PP No. 55 of 2022 and tax socialization simultaneously have a positive and  significant effect on the tax compliance of SMEs by 67.9%.